Energy-saving and environment-friendly strong pervious concrete and preparation method thereof

By composting the regenerated crude aggregates with isobutyltriethoxysilane, the strength and permeability of permeable concrete are improved, the problem of low density of permeable concrete is solved, and the load-bearing capacity is achieved and transportation efficiency.

CN119306443AActive Publication Date: 2025-01-14SINAN QIANGLI ELECTRIC POLE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411433628.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Due to the large number of voids, permeable concrete leads to low density, reduced strength and insufficient load-bearing capacity, which limits the development of vehicle load and transportation.

Method used

The regenerated crude aggregate is modified by using isobutyltriethoxysilane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate compound modifier to improve its bonding ability with cement. The strength of permeable concrete is significantly improved while maintaining high permeability.

Benefits of technology

It significantly improves the strength of permeable concrete and road load-bearing capacity, enhances the development prospects of transportation, and controls costs, and has high economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005084350660000081
    Figure BDA0005084350660000081
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly discloses energy-saving and environment-friendly strong pervious concrete and a preparation method thereof. The invention relates to energy-saving and environment-friendly strong pervious concrete, which comprises the following components in parts by mass: 100 parts of water; 256 to 260 parts of cement; 27 to 29 parts of fly ash; 1080 to 1090 parts of modified recycled coarse aggregate; 4.4 to 4.8 parts of an additive; the modified recycled coarse aggregate is prepared by modifying recycled coarse aggregate with a modifier; the recycled coarse aggregate is formed by breaking waste concrete; and the modifier is a compound of isobutyl triethoxy silane, cyclohexyl methacrylate, 2-ethylhexyl acrylate and hydroxyethyl acrylate. The method has the advantage of improving the strength of the pervious concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to energy-saving, environment-friendly, highly permeable concrete and a preparation method thereof. Background Art

[0002] Permeable concrete is also called sand-free concrete. Coarse aggregate is used in permeable concrete, which makes the permeable concrete have a certain porosity after curing, so that water can pass through the concrete smoothly, and can achieve better drainage, anti-skid, sound absorption, noise reduction and other effects, effectively improve the surface ecological cycle, and benefit driving traffic safety.

[0003] However, due to the presence of a large number of voids in permeable concrete, the density of permeable concrete is relatively low, and the strength of ordinary concrete is mainly improved through its density, which leads to a significant decrease in the strength of general permeable concrete. Permeable concrete is mainly used for road paving. The decrease in the strength of permeable concrete leads to a decrease in its bearing capacity, thereby limiting the vehicle load and affecting the development of transportation. Therefore, there is still room for improvement. Summary of the invention

[0004] In order to improve the strength of permeable concrete, the present application provides an energy-saving and environmentally friendly highly permeable concrete and a preparation method thereof.

[0005] In the first aspect, the present application provides an energy-saving and environmentally friendly highly permeable concrete, which adopts the following technical solution: An energy-saving and environment-friendly highly permeable concrete comprises the following components in parts by weight: 100 parts water; Cement 256-260 parts; Fly ash 27-29 parts; Modified recycled coarse aggregate 1080-1090 parts; Admixture 4.4-4.8 parts; The modified recycled coarse aggregate is prepared by modifying the recycled coarse aggregate with a modifier; The recycled coarse aggregate is made from broken waste concrete; The modifier is a compound of isobutyl triethoxy silane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate.

[0006] By adopting the above technical scheme, the recycled coarse aggregate is modified by using a modifier composed of isobutyltriethoxysilane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate, so that the bonding ability between the recycled coarse aggregate and cement can be improved, and the cement and the recycled coarse aggregate are not easy to be separated, thereby significantly improving the strength of the permeable concrete, maintaining high permeability while better improving the bearing capacity of the road surface, and being more conducive to the development of transportation.

[0007] Preferably, the mass ratio of isobutyltriethoxysilane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate is 15-17:3-5:7-9:4-6.

[0008] By adopting the above technical scheme and specifically selecting the mass ratio of isobutyltriethoxysilane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate, the modification effect on the recycled coarse aggregate is better and the strength of the permeable concrete is better improved.

[0009] Preferably, the particle size of the recycled coarse aggregate is 8-10 mm.

[0010] By adopting the above technical solution, by specifically selecting the particle size of the recycled coarse aggregate to be 8-10mm, the voids formed have higher drainage performance, and it is not easy to form local large holes, so that the performance of the permeable concrete is evenly distributed, which is conducive to improving stability and higher strength.

[0011] Preferably, the modification method of the modified recycled coarse aggregate is as follows: Step 1), isobutyl triethoxysilane, cyclohexyl methacrylate, isooctyl acrylate, and hydroxyethyl acrylate are uniformly mixed to obtain a modifier; Step 2), put the recycled coarse aggregate into the modifier, heat it to 130-140°C, keep the temperature at 130-140°C, and soak it for 3-4 hours.

[0012] By adopting the above technical solution, by heating to 130-140°C, the modification effect is more significant, the modified recycled aggregate is less likely to be separated from the cement, and is better connected to form a whole, thereby making the strength of the permeable concrete higher.

[0013] Preferably, in step 2), the mass ratio of recycled coarse aggregate to modifier is 1:1.5-2.

[0014] By adopting the above technical scheme and specifically selecting the mass ratio of recycled coarse aggregate to modifier, the modifier can fully infiltrate the recycled coarse aggregate, ensuring a better modification effect, while reducing the waste of modifier, better controlling costs, and having a higher economic value.

[0015] Preferably, in the step 2), during the soaking and modification process, the rotation speed is 20-30 r / min and stirring is continued.

[0016] By adopting the above technical solution and through continuous stirring, the modification effect is more sufficient and the strength of the permeable concrete is higher.

[0017] Preferably, the admixture is a compound of a water reducing agent and an early strength agent, and the mass ratio of the water reducing agent to the early strength agent is 3.2-3.4:1.2-1.4.

[0018] By adopting the above technical scheme and specifically selecting water reducing agent and early strength agent, the construction performance of permeable concrete is improved and water seepage is reduced. At the same time, the early strength agent can make the concrete form a stable structure more quickly, so that the concrete can better maintain a high permeability after solidification.

[0019] Preferably, the water reducer is a polycarboxylate water reducer; and the early strength agent is calcium formate.

[0020] By adopting the above technical scheme and specifically selecting the polycarboxylate water-reducing agent and the early strength agent as calcium formate, the water-reducing and early strength effects are better, and the performance of the permeable concrete is better.

[0021] In a second aspect, the present application provides a method for preparing energy-saving and environmentally friendly highly permeable concrete, which adopts the following technical solution: A method for preparing the above-mentioned energy-saving and environment-friendly highly permeable concrete comprises the following steps: Step 01), cement, fly ash, modified recycled coarse aggregate and admixture are mixed uniformly to obtain a premix; Step 02), adding water to the premix and mixing evenly to obtain a concrete mixture; Step 03), pouring the concrete mixture into the mold, curing and demoulding, to obtain energy-saving, environmentally friendly and highly permeable concrete.

[0022] By adopting the above technical solution, the permeable concrete obtained has high permeability and high strength, is particularly suitable for use in roads, can effectively improve the road bearing capacity, and the obtained road surface is not easy to crack, and has a high application prospect.

[0023] In summary, this application has the following beneficial effects: 1. Since the present application modifies the recycled coarse aggregate by using a modifier composed of isobutyl triethoxysilane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate, the bonding ability between the recycled coarse aggregate and cement can be improved, making it difficult for cement and the recycled coarse aggregate to peel off, thereby significantly improving the strength of the permeable concrete, maintaining high permeability while better improving the bearing capacity of the road surface, and being more conducive to the development of transportation.

[0024] 2. In the present application, it is preferred to specifically select the mass ratio of isobutyltriethoxysilane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate so as to achieve a better modification effect on the recycled coarse aggregate and better improve the strength of the permeable concrete.

[0025] 3. In the present application, it is preferred that the particle size of the recycled coarse aggregate is 8-10 mm, so that the voids formed have higher drainage performance and are not prone to forming local large holes, so that the performance of the permeable concrete is evenly distributed, which is conducive to improving stability and higher strength. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] Example 1 An energy-saving and environment-friendly highly permeable concrete comprises the following components: Water, cement, fly ash, modified recycled coarse aggregate, admixtures.

[0028] The cement was purchased from Runfeng Cement, silicate cement, P.O42.5R.

[0029] The fly ash is sourced from commercially available, first-grade fly ash.

[0030] The admixture is a compound of water reducing agent and early strength agent.

[0031] The water reducer is polycarboxylic acid water reducer, purchased from Wuhan Huaxuan High-tech Co., Ltd., model: PC-306.

[0032] The early strength agent is calcium formate, which was purchased from Henan Mingzhixin Chemical Products Co., Ltd.

[0033] Modified recycled coarse aggregate is prepared by modifying recycled coarse aggregate with a modifier.

[0034] Recycled coarse aggregate is made from broken waste concrete, and the particle size of recycled coarse aggregate is 8-10mm.

[0035] The modifier is a compound of isobutyl triethoxy silane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate.

[0036] Isobutyltriethoxysilane was purchased from Shandong Yuanjin New Materials Co., Ltd.

[0037] Cyclohexyl methacrylate was purchased from Changzhou Aozun Composite New Materials Co., Ltd.

[0038] Isooctyl acrylate was purchased from Shandong Ruigang Chemical Co., Ltd.

[0039] Hydroxyethyl acrylate was purchased from Shandong Youwang Chemical Products Co., Ltd.

[0040] The modification method of modified recycled coarse aggregate is as follows: Step 1), 1500kg of isobutyltriethoxysilane, 300kg of cyclohexyl methacrylate, 700kg of isooctyl acrylate, and 400kg of hydroxyethyl acrylate are put into a stirring tank, the speed is 60r / min, stirred for 10min, and mixed evenly to obtain a modifier.

[0041] Step 2), 1933 kg of recycled coarse aggregate is put into the modifier, heated to 130°C, kept at a constant temperature of 130°C, a rotation speed of 20 r / min, continuously stirred, modified for 3 hours, the solid is filtered out, and ventilated at 110°C for 2 hours to obtain modified recycled coarse aggregate.

[0042] The preparation method of energy-saving and environment-friendly highly permeable concrete comprises the following steps: Step 01), put 256kg cement, 27kg fly ash, 1080kg modified recycled coarse aggregate, 3.2kg water reducer, and 1.2kg early strength agent into a concrete mixer, rotate at 60r / min, stir for 15min, mix evenly, and obtain a premix.

[0043] Step 02), add 100kg water to the premix, rotate at 60r / min, stir for 5min, mix evenly, and obtain concrete mixture.

[0044] Step 03), pour the concrete mixture into the mold, sprinkle water for 3 days, demould, sprinkle water for 7 days, and stand for 28 days to obtain energy-saving and environmentally friendly highly permeable concrete.

[0045] Example 2 An energy-saving and environment-friendly highly permeable concrete comprises the following components: Water, cement, fly ash, modified recycled coarse aggregate, admixtures.

[0046] The cement was purchased from Runfeng Cement, silicate cement, P.O42.5R.

[0047] The fly ash is sourced from commercially available, first-grade fly ash.

[0048] The admixture is a compound of water reducing agent and early strength agent.

[0049] The water reducer is polycarboxylic acid water reducer, purchased from Wuhan Huaxuan High-tech Co., Ltd., model: PC-306.

[0050] The early strength agent is calcium formate, which was purchased from Henan Mingzhixin Chemical Products Co., Ltd.

[0051] Modified recycled coarse aggregate is prepared by modifying recycled coarse aggregate with a modifier.

[0052] Recycled coarse aggregate is made from broken waste concrete, and the particle size of recycled coarse aggregate is 8-10mm.

[0053] The modifier is a compound of isobutyl triethoxy silane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate.

[0054] Isobutyltriethoxysilane was purchased from Shandong Yuanjin New Materials Co., Ltd.

[0055] Cyclohexyl methacrylate was purchased from Changzhou Aozun Composite New Materials Co., Ltd.

[0056] Isooctyl acrylate was purchased from Shandong Ruigang Chemical Co., Ltd.

[0057] Hydroxyethyl acrylate was purchased from Shandong Youwang Chemical Products Co., Ltd.

[0058] The modification method of modified recycled coarse aggregate is as follows: Step 1), 1600 kg of isobutyltriethoxysilane, 400 kg of cyclohexyl methacrylate, 800 kg of isooctyl acrylate, and 500 kg of hydroxyethyl acrylate are put into a stirring tank, the speed is 60 r / min, stirred for 10 min, and mixed evenly to obtain a modifier.

[0059] Step 2), 1885 kg of recycled coarse aggregate is added to the modifier, heated to 135°C, kept at a constant temperature of 135°C, a rotation speed of 25 r / min, continuously stirred, modified for 3.5 hours, the solid is filtered out, and ventilated at 110°C for 2 hours to obtain modified recycled coarse aggregate.

[0060] The preparation method of energy-saving and environment-friendly highly permeable concrete comprises the following steps: Step 01), put 258kg cement, 28kg fly ash, 1085kg modified recycled coarse aggregate, 3.3kg water reducer, and 1.3kg early strength agent into a concrete mixer, rotate at 60r / min, stir for 15min, mix evenly, and obtain a premix.

[0061] Step 02), add 100kg water to the premix, rotate at 60r / min, stir for 5min, mix evenly, and obtain concrete mixture.

[0062] Step 03), pour the concrete mixture into the mold, sprinkle water for 3 days, demould, sprinkle water for 7 days, and stand for 28 days to obtain energy-saving and environmentally friendly highly permeable concrete.

[0063] Example 3 An energy-saving and environment-friendly highly permeable concrete comprises the following components: Water, cement, fly ash, modified recycled coarse aggregate, admixtures.

[0064] The cement was purchased from Runfeng Cement, silicate cement, P.O42.5R.

[0065] The fly ash is sourced from commercially available, first-grade fly ash.

[0066] The admixture is a compound of water reducing agent and early strength agent.

[0067] The water reducer is polycarboxylic acid water reducer, purchased from Wuhan Huaxuan High-tech Co., Ltd., model: PC-306.

[0068] The early strength agent is calcium formate, which was purchased from Henan Mingzhixin Chemical Products Co., Ltd.

[0069] Modified recycled coarse aggregate is prepared by modifying recycled coarse aggregate with a modifier.

[0070] Recycled coarse aggregate is made from broken waste concrete, and the particle size of recycled coarse aggregate is 8-10mm.

[0071] The modifier is a compound of isobutyl triethoxy silane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate.

[0072] Isobutyltriethoxysilane was purchased from Shandong Yuanjin New Materials Co., Ltd.

[0073] Cyclohexyl methacrylate was purchased from Changzhou Aozun Composite New Materials Co., Ltd.

[0074] Isooctyl acrylate was purchased from Shandong Ruigang Chemical Co., Ltd.

[0075] Hydroxyethyl acrylate was purchased from Shandong Youwang Chemical Products Co., Ltd.

[0076] The modification method of modified recycled coarse aggregate is as follows: Step 1), 1700 kg of isobutyltriethoxysilane, 500 kg of cyclohexyl methacrylate, 900 kg of isooctyl acrylate, and 600 kg of hydroxyethyl acrylate are put into a stirring tank, the speed is 60 r / min, stirring for 10 min, and mixing evenly to obtain a modifier.

[0077] Step 2), 1850 kg of recycled coarse aggregate is put into the modifier, heated to 140°C, kept at a constant temperature of 140°C, a rotation speed of 30 r / min, continuously stirred, modified for 4 hours, the solid is filtered out, and ventilated at 110°C for 2 hours to obtain modified recycled coarse aggregate.

[0078] The preparation method of energy-saving and environment-friendly highly permeable concrete comprises the following steps: Step 01), put 260kg cement, 29kg fly ash, 1090kg modified recycled coarse aggregate, 3.4kg water reducer, and 1.4kg early strength agent into a concrete mixer, rotate at 60r / min, stir for 15min, mix evenly, and obtain a premix.

[0079] Step 02), add 100kg water to the premix, rotate at 60r / min, stir for 5min, mix evenly, and obtain concrete mixture.

[0080] Step 03), pour the concrete mixture into the mold, sprinkle water for 3 days, demould, sprinkle water for 7 days, and stand for 28 days to obtain energy-saving and environmentally friendly highly permeable concrete.

[0081] Comparative Example 1 An energy-saving and environment-friendly highly permeable concrete, compared with Example 2, the only difference is: In the modifier, methyltrimethoxysilane is used to replace isobutyltriethoxysilane in equal amounts.

[0082] Methyltrimethoxysilane was purchased from Shandong Yuanjin New Materials Co., Ltd.

[0083] Comparative Example 2 An energy-saving and environment-friendly highly permeable concrete, compared with Example 2, the only difference is: In the modifier, cyclohexyl methacrylate is replaced by an equal amount of stearic acid acrylate.

[0084] Acrylic stearate was purchased from Shandong Jinyufeng New Materials Co., Ltd.

[0085] Comparative Example 3 An energy-saving and environment-friendly highly permeable concrete, compared with Example 2, the only difference is: In the modifier, dipropylene glycol diacrylate is used to replace isooctyl acrylate in an equal amount.

[0086] Dipropylene glycol diacrylate was purchased from Hubei Biaoyue Biotechnology Development Co., Ltd.

[0087] Comparative Example 4 An energy-saving and environment-friendly highly permeable concrete, compared with Example 2, the only difference is: In the modifier, trimethylolpropane trimethacrylate is used to replace hydroxyethyl acrylate in an equal amount.

[0088] Trimethylolpropane trimethacrylate was purchased from Hubei Tosoh Chemical Technology Co., Ltd.

[0089] Comparative Example 5 An energy-saving and environment-friendly highly permeable concrete, compared with Example 2, the only difference is: In the modifier, methyltrimethoxysilane is used to replace isobutyltriethoxysilane in an equal amount, stearic acid acrylate is used to replace cyclohexyl methacrylate in an equal amount, dipropylene glycol diacrylate is used to replace isooctyl acrylate in an equal amount, and trimethylolpropane trimethacrylate is used to replace hydroxyethyl acrylate in an equal amount.

[0090] Methyltrimethoxysilane was purchased from Shandong Yuanjin New Materials Co., Ltd.

[0091] Acrylic stearate was purchased from Shandong Jinyufeng New Materials Co., Ltd.

[0092] Dipropylene glycol diacrylate was purchased from Hubei Biaoyue Biotechnology Development Co., Ltd.

[0093] Trimethylolpropane trimethacrylate was purchased from Hubei Tosoh Chemical Technology Co., Ltd.

[0094] Comparative Example 6 An energy-saving and environment-friendly highly permeable concrete comprises the following components: Water, cement, fly ash, coarse aggregate, admixtures.

[0095] The cement was purchased from Runfeng Cement, silicate cement, P.O42.5R.

[0096] The fly ash is sourced from commercially available, first-grade fly ash.

[0097] The admixture is a compound of water reducing agent and early strength agent.

[0098] The water reducer is polycarboxylic acid water reducer, purchased from Wuhan Huaxuan High-tech Co., Ltd., model: PC-306.

[0099] The early strength agent is calcium formate, which was purchased from Henan Mingzhixin Chemical Products Co., Ltd.

[0100] The coarse aggregate is basalt crushed stone, which is commercially available and has a particle size of 8-10 mm.

[0101] The preparation method of energy-saving and environment-friendly highly permeable concrete comprises the following steps: Step 01), put 258kg cement, 28kg fly ash, 1085kg coarse aggregate, 3.3kg water reducer and 1.3kg early strength agent into a concrete mixer, rotate at 60r / min, stir for 15min, mix evenly, and obtain a premix.

[0102] Step 02), add 100kg water to the premix, rotate at 60r / min, stir for 5min, mix evenly, and obtain concrete mixture.

[0103] Step 03), pour the concrete mixture into the mold, sprinkle water for 3 days, demould, sprinkle water for 7 days, and stand for 28 days to obtain energy-saving and environmentally friendly highly permeable concrete.

[0104] Experiment 1 According to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 7-day compressive strength, 28-day compressive strength, and 28-day splitting tensile strength of the test samples made of concrete in each embodiment and comparative example were tested.

[0105] Experiment 2 According to GB / T25993-2010 "Permeable Pavement Bricks and Permeable Road Slabs", the permeability levels of concrete samples prepared from the concrete mixtures of the embodiments and comparative examples were tested.

[0106] Grade A: Water permeability coefficient ≥ 2.0×10 -2 .

[0107] Class B: Water permeability coefficient ≥1.0×10 -2 .

[0108] The specific test data of Experiments 1 and 2 are shown in Table 1.

[0109] Table 1 According to the data comparison between the embodiments and the comparative examples in Table 1, the water permeability of the embodiments and the comparative examples is better, and the strength of the embodiments is significantly higher than that of the comparative examples, especially higher than that of comparative example 6. Comparative example 6 is a concrete made of natural stone, while the embodiments use recycled coarse aggregate modified by a modifier prepared by compounding isobutyl triethoxysilane, cyclohexyl methacrylate, isooctyl acrylate, and hydroxyethyl acrylate. The strength of the concrete is higher than that of comparative example 6 using natural stone. It can be seen that the modifier prepared by compounding isobutyl triethoxysilane, cyclohexyl methacrylate, isooctyl acrylate, and hydroxyethyl acrylate can significantly improve the connection between the recycled coarse aggregate and the cement stone, so that the strength of the concrete after curing is significantly improved.

[0110] In Comparative Examples 1-5, the compounding system of isobutyltriethoxysilane, cyclohexyl methacrylate, isooctyl acrylate, and hydroxyethyl acrylate was destroyed, resulting in the concrete strength made from the modified recycled coarse aggregate being only barely close to that of Comparative Example 6 using natural aggregate. It can be seen that the modification effect brought about by the compounding of butyltriethoxysilane, cyclohexyl methacrylate, isooctyl acrylate, and hydroxyethyl acrylate is excellent, and replacing any one of them will lead to a significant decrease in the modification effect.

[0111] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. An energy-saving and environment-friendly highly permeable concrete, characterized by: The composition includes the following components in parts by weight: 100 parts water; Cement 256-260 parts; Fly ash 27-29 parts; Modified recycled coarse aggregate 1080-1090 parts; Admixture 4.4-4.8 parts; The modified recycled coarse aggregate is prepared by modifying the recycled coarse aggregate with a modifier; The recycled coarse aggregate is made from broken waste concrete; The modifier is a compound of isobutyl triethoxy silane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate.

2. The energy-saving and environment-friendly highly permeable concrete according to claim 1, characterized in that: The mass ratio of the isobutyl triethoxysilane, cyclohexyl methacrylate, isooctyl acrylate and hydroxyethyl acrylate is 15-17:3-5:7-9:4-6.

3. The energy-saving and environment-friendly highly permeable concrete according to claim 2 is characterized in that: The particle size of recycled coarse aggregate is 8-10mm.

4. The energy-saving and environment-friendly highly permeable concrete according to claim 3 is characterized in that: The modification method of the modified recycled coarse aggregate is as follows: Step 1), isobutyl triethoxysilane, cyclohexyl methacrylate, isooctyl acrylate, and hydroxyethyl acrylate are uniformly mixed to obtain a modifier; Step 2) Place the recycled coarse aggregate into the modifier, heat to 130-140°C, maintain a constant temperature of 130-140°C, and soak for 3-4 hours.

5. The energy-saving and environment-friendly highly permeable concrete according to claim 4, characterized in that: In the step 2), the mass ratio of the recycled coarse aggregate to the modifier is 1:1.5-2.

6. The energy-saving and environment-friendly highly permeable concrete according to claim 5, characterized in that: In the step 2), during the soaking and modification process, the rotation speed is 20-30 r / min and stirring is continued.

7. The energy-saving and environment-friendly highly permeable concrete according to claim 1, characterized in that: The admixture is a compound of a water reducing agent and an early strength agent, and the mass ratio of the water reducing agent to the early strength agent is 3.2-3.4:1.2-1.

4.

8. The energy-saving and environment-friendly highly permeable concrete according to claim 7, characterized in that: The water reducer is a polycarboxylate water reducer; and the early strength agent is calcium formate.

9. A method for preparing energy-saving and environment-friendly highly permeable concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 01), cement, fly ash, modified recycled coarse aggregate and admixture are uniformly mixed to obtain a premix; Step 02), adding water to the premix and mixing evenly to obtain a concrete mixture; Step 03), pour the concrete mixture into the mold, maintain and demould, and obtain energy-saving, environmentally friendly and highly permeable concrete.

Citation Information

Patent Citations

  • Pervious concrete system applying construction waste and preparation method of pervious concrete

    CN109111155A

  • Bare concrete produced from construction waste recycled aggregate

    CN112830740A

  • Recycled concrete and preparation method thereof

    CN116161929A

  • The manufacture method of the recycled additive added the polymer complex used cold recycled asphalt mixture

    KR101230863B1